Pengaruh Variasi Jarak Nosel dan Kecepatan Udara Inlet terhadap Tekanan dan Kecepatan Hisap pada Pompa Vakum Jet Ejector - Arasy Fahruddin; Lukman Hudi; Bambang Surono; Mulyadi Mulyadi (TURBO [Tulisan Riset Berbasis Online], 2026)
This study aims to analyze the effect of variations in nozzle spacing and inlet air velocity on the vacuum pressure and flow velocity distribution in a jet ejector vacuum pump. The method used is a numerical simulation based on Computational Fluid Dynamics (CFD) to obtain a detailed picture of the fluid flow characteristics in the system. The variations in nozzle spacing studied include 14 mm, 16 mm, and 18 mm, while the inlet air velocity is varied at 10 m/s, 15 m/s, and 20 m/s. The simulation results show that increasing the nozzle spacing tends to reduce the pressure on the venturi, thereby increasing the vacuum effect, with optimal conditions obtained at a distance of 18 mm and an inlet velocity of 10 m/s. Under these conditions, the pressure in the tube reaches the lowest value compared to other variations. However, increasing the inlet air velocity actually causes an increase in pressure in the tube due to turbulence and backflow, thereby reducing or even eliminating the vacuum effect at velocities of 15 m/s and 20 m/s. Overall, the performance of a jet ejector is greatly influenced by a combination of geometric and operational parameters.